Aggregate demand, functional finance and secular stagnation - Peter Skott (University of Massachusetts, Department of Economics, 2016)
This paper makes three main points. Fiscal policy, first, may be needed in the long run to maintain full employment and avoid secular stagnation. If fiscal policy is used in this way, second, the long-run debt ratio depends (i) inversely on the rate of growth, (ii) inversely on government consumption, and (iii) directly on the degree of inequality. The analysis, third, suggests that policies and policy debates have been misguided. The recent rediscovery of 'secular stagnation' by Summers and others should be welcomed, but the suggested theoretical redirection is unclear and does not go far enough.
Keywords: E62; E22; 330; functional finance; zero lower bound; liquidity trap; fiscal policy; secular stagnation; austerity; public debt